473. Molecular Typing of Clostridium difficile: Concordance Between PCR-Ribotyping and Multilocus Sequence Typing (MLST). (26th November 2018) - Wang, Xiong; Holzbauer, Stacy; Pung, Kelly; Bye, Maria; Adamczyk, Michelle; Paulick, Ashley Lyn; Vlachos, Nicholas; Guh, Alice; Laufer-Halpin, Alison S; Karlsson, Maria S; Boxrud, Dave; ,
Abstract: Background: Clostridium difficile infection (CDI) incidence has increased dramatically in the past decade, making CDI one of the most common causes of infectious diarrhea and an urgent public health threat. Understanding the biological features and spread of C. difficile strains can help target control efforts. PCR-ribotyping, the current method of choice for C. difficile typing, remains subjective and challenging for interlaboratory comparisons. Multilocus sequence typing (MLST), based on the alleles of seven housekeeping genes, represents a more robust tool that would enhance interlaboratory reproducibility. However, a comprehensive translation system to ribotyping is a prerequisite. Here, we describe the concordance between MLST and PCR-ribotyping. Methods: The Centers for Disease Control and Prevention's (CDC) Emerging Infections Program (EIP) conducts CDI surveillance in 10 US sites. C. difficile isolates cultured from a subset of cases underwent capillary-based PCR-ribotyping at CDC. A representative sample, selected from the top 30 ribotypes (RTs), underwent whole genome sequencing (WGS) at Minnesota Department of Health. An additional subset of isolates, representing the top 10 RTs, underwent WGS at CDC. At both laboratories, the Illumina MiSeq platform was used to obtain 250 bp paired-end sequencing reads. MLST analyses were done using the pubMLST C. difficile scheme. Results: A total of 479 C. difficile isolates, including at least 10 isolates for each RT, were analyzed by WGS. Among the 30 RTs represented, 35 different MLST sequence types (STs) were identified. Twenty-two of the RTs (including 027) were each associated with a single unique ST, while 8 RTs (020, 014, 015, 076, 046, 153–251, A27, and 075) presented more genetic diversity with single-locus or double-locus variants, resulting in multiple STs within one ribotype. There were two instances of two different RTs sharing the same ST. Conclusion: Multilocus sequence typing and PCR-Ribotyping showed comparable discriminatory abilities. However, the ST is not always predictive of the RT and vice versa. This represents the first step toward a transition to using WGS for standard C. difficile typing. Disclosures: All authors: No reported disclosures.